Factors influencing Ontario dairy veterinarians’ management and care of down dairy cows - Brindle, John E.; Renaud, David L.; Haley, Derek B.; Duffield, Todd F.; Winder, Charlotte B. (Frontiers in Veterinary Science, 2025)
This cross-sectional study assessed what management practices veterinarians recommended for down dairy cows in Ontario, Canada, and identified factors influencing producers’ adoption of protocols. An online survey about veterinary involvement in down cow management was available between February and May 2021, distributed by email through the Ontario Association of Bovine Practitioners (OABP). A total of 48 Ontario bovine veterinarians responded (26.8% response rate). Gender distribution was even between those identifying as male or female (50%), and the majority of respondents were between 30 to 39 years old. Veterinarians most commonly suggested housing down dairy cows in individual pens (40.7%), followed by pasture (29.6%), special pens for three or fewer animals (26%), and special pens for four or more animals (3.7%). Regarding spacing allowance for a down dairy cow, many veterinarians suggested 11.1 (120) to 23.2 (120–250 square feet) square meters (53.3%) per cow. Recommendations for moving down dairy cows included using a sled (62.5%), stone boat (56.3%), front-end loader bucket (45.8%), wheeled cart (20.8%), and hip-lifter (2.1%). For lifting down dairy cows, recommendations included using multiband slings (56.2%), hip lifters (43.8%), floatation tanks (25.0%), single belly slings (14.6%), ropes (4.2%), and hip lifters with additional straps (2.1%). A multivariable linear regression model identified key factors associated with the recommended time to assist a down cow to stand. Specifically, veterinarians who spent over 90% of their working hours annually with dairy cattle recommended assisting cows 14.1 h earlier than those who spent less than 85% of their time working with dairy cattle. Additionally, larger clinics advised waiting 12.4 h longer compared to smaller clinics, and veterinarians who recommended waiting 12–24 h before calling a veterinarian suggested assisting cows 13.8 h later than those recommending a wait of less than 7 h. Implementing a more consistent, evidence-based approach by veterinarians could enhance the care of down dairy cows and support the broader objective of improving management protocols.